Smart Farmer Sebagai Optimalisasi Digital Platform Dalam Pemasaran Produk Pertanian Pada Masa Pandemi Covid-19 - Sibarani, Blasius Erik (Technomedia Journal, 2021)
Agriculture is one of the sectors that can boost the nation's economic condition during the Covid-19 pandemic. However, during the covid-19 pandemic, there are still many farming communities who lack access to marketing their agricultural products. Marketing is one of the factors in increasing the sales of the farming community. Without easy marketing access, farmers 'products are not known by the wider community so that farmers' sales do not increase which will have an impact on the economy. Of course, this situation really needs to be improved, so that farmer products can be recognized and can be sold outside the region so that it can encourage the level of economic turnover during the Covid-19 pandemic. One of the efforts to improve this is by building a digital platform that can be used by farmers to market their products. The benefits obtained by farmers as well as consumers directly and indirectly, especially from the wider access to marketing agricultural products can increase production demand and accelerate the procurement of production among farmers and also the price offered to consumers according to market prices so that sales agricultural yields can increase and benefit farmers. The purpose of this paper is to provide ideas in product marketing for farmers during the Covid-19 pandemic to be able to sustain the nation's economy. Key words: Covid-19, Digital Platform, Marketing, Agriculture